Symbolic Legitimacy Without Elections: A Computational Framing Analysis of the Bureaucratic Branding Practices of Non-Elected Officials on Social Media (Case Study of Teddy Indra Wijaya) - Rizky Saputra; Andri Yoga Pratama; Edison Bonartua Hutapea (CV. Publikasi Indonesia, 2026)
This study analyzes the phenomenon of bureaucratic branding on non-electoral officials in the context of digital political communication in Indonesia through a case study of the